PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT BELI MAHASISWA SEBAGAI KONSUMEN POTESIAL PRODUK PASTA GIGI PEPSODENT - Fakultas Ekonomi Universitas Slamet Riyadi Surakarta, Rahayu Triastity, Sumarno Dwi Saputro (MAJALAH ILMIAH GEMA, 2013)
Target of this research is (1) to significant influence consumer attitude and subjective normapartial or simultan to customer buying intentions.This research type is quantitative, that is research which aim to obtain from hypothesis byusing predicted parameter test (test t) to test question instrument used by validity test and reliabilitytest. While classic assumption test which used by multikolinieritas, autocorrelation, heterokedastisitasand normalitas. Result of research show (1) Examination of hypothesis by partial (test t) variable be as followed attitude variable and norma variable have an effect significant to consumer buying intention. (2) Examination of hypotesis accuracy of model (F test) show F value correlated equal to = 29,368 with, level of significant 0,000 probability value 0,000 < 0,05 makes give meaning that exemption of used by model that is attitude and subjectives norma have on effect significant to consumer buying intentions. Result from assumption classical test conclude used regression model in this research donot happened. Multicolineritas, Autocorelation, Heteroskedastititas and than can be said blue.Key word : customer attitude, subjective norma and consumer buying intentions